2018
DOI: 10.1002/ejp.1284
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy, acceptability and safety of Internet‐delivered psychological therapies for fibromyalgia syndrome: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Internet-delivered cognitive behavioural therapies provided a clinically relevant benefit in reducing negative mood and disability in patients with FMS at the end of treatment if compared to waiting list, treatment as usual and attention controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 39 publications
1
34
0
2
Order By: Relevance
“…Results from Study II was also slightly higher than the between-group effect sizes reported by other studies on fatigue, sleep problems and the risk difference (RD) in attaining ≥50% pain relief (RD 0.27) and a ≥20% improvement of health-related quality of life (RD 0.31) in a recent review and meta-analysis on internet-delivered psychological therapies for FM (≥50% pain relief RD 0.10; ≥20% improvement of health-related quality of life RD 0.22). 133 With the exception of a recent Dutch study, 109 results from Study II are also comparable to previous randomized controlled trials of exposure therapy for other chronic pain conditions (although it should be noted that the primary outcome in Study II differs from previous trials, i.e., by also covering FM symptoms other than pain and painrelated disability). As described previously though, the iExp treatment manual differ from existing exposure protocols for chronic pain.…”
Section: Is Internet-delivered Exposure Therapy Acceptable and Effectsupporting
confidence: 53%
“…Results from Study II was also slightly higher than the between-group effect sizes reported by other studies on fatigue, sleep problems and the risk difference (RD) in attaining ≥50% pain relief (RD 0.27) and a ≥20% improvement of health-related quality of life (RD 0.31) in a recent review and meta-analysis on internet-delivered psychological therapies for FM (≥50% pain relief RD 0.10; ≥20% improvement of health-related quality of life RD 0.22). 133 With the exception of a recent Dutch study, 109 results from Study II are also comparable to previous randomized controlled trials of exposure therapy for other chronic pain conditions (although it should be noted that the primary outcome in Study II differs from previous trials, i.e., by also covering FM symptoms other than pain and painrelated disability). As described previously though, the iExp treatment manual differ from existing exposure protocols for chronic pain.…”
Section: Is Internet-delivered Exposure Therapy Acceptable and Effectsupporting
confidence: 53%
“…Online delivery can make interventions more accessible to patients e.g. in rural areas since logistic barriers such as travel or limited access to trained therapists are eliminated [44]. As reported in S8, Simister et al [42] obtained 100% adherence which might support further development and exploration of online interventions for FM in future research.…”
Section: Discussionmentioning
confidence: 92%
“…A power analysis for the group comparison iSOMA versus WLCG using analysis of covariance (ANCOVA) with baseline scores as covariates, an α error of 0.05 and a power of β=0.80 showed that a sample size of n=128 is required. Considering attrition rates of previous trials, for example, in functional somatic syndromes,97 chronic pain98 or various chronic health conditions99 as well as recent trials in the relevant target group of university students,29 a drop-out rate of 20% is expected for the current trial, resulting in a necessary sample size of n=154 (n=77 per group). The estimated sample size is suitable regarding prevalence rates of the somatoform syndrome45 and somatoform disorders in German university students 46…”
Section: Methodsmentioning
confidence: 99%